Insight as a social identity process in the evolution of psychosocial functioning in the early phase of psychosis. Issue 4 (21st November 2016) - Klaas, H. S.; Clémence, A.; Marion-Veyron, R.; Antonietti, J.-P.; Alameda, L.; Golay, P.; Conus, P.
Abstract : Background: Awareness of illness (insight) has been found to have contradictory effects for different functional outcomes after the early course of psychosis. Whereas it is related to psychotic symptom reduction and medication adherence, it is also associated with increased depressive symptoms. In this line, the specific effects of insight on the evolution of functioning over time have not been identified, and social indicators, such as socio-occupational functioning have barely been considered. Drawing from social identity theory we investigated the impact of insight on the development of psychosocial outcomes and the interactions of these variables over time. Method: The participants, 240 patients in early phase of psychosis from the Treatment and Early Intervention in Psychosis Program (TIPP) of the University Hospital of Lausanne, Switzerland, were assessed at eight time points over 3 years. Cross-lagged panel analyses and multilevel analyses were conducted on socio-occupational and general functioning [Social and Occupational Functioning Assessment Scale (SOFAS) and Global Assessment of Functioning (GAF)] with insight, time and depressive symptoms as independent variables. Results: Results from multilevel analyses point to an overall positive impact of insight on psychosocial functioning, which increases over time. Yet the cross-lagged panel analysis did not reveal a systematic positive and causal effect of insight on SOFAS and GAF scores. Depressive symptoms seem only to be relevant in the beginning of the treatment process. Conclusions: Our results point to a complex process in which the positive impact of insight on psychosocial functioning increases over time, even when considering depressive symptoms. Future studies and treatment approaches should consider the procedural aspect of insight.